Vaccination against the hepatitis B virus in newborns of peruvian women participating in the demographic and family health survey, 2016 - Roque Henriquez, Joel Christian (2018)
Introduction. The national vaccination scheme in Peru includes the hepatitis B vaccine at birth, the World Health Organization established goals for the coverage of this vaccination. The objective of the study was to estimate the proportion of newborns of women participating in the Demographic and Family Health Survey (ENDES) of Peru in 2016, who received vaccination against hepatitis B. Methods. A secondary study was conducted, the informants subject were childbearing age women from 15 to 49 years old, who reported having a child under five years of age, whose weight at birth was 2000g or more, and who have data regarding vaccination. The data on vaccination status against hepatitis B was obtained from the vaccination card. The results are presented for the national, regional level, and according to some specific sub groups. Results. At the national level, 67,5% (95% CI: 66,3-68,6) of newborns received vaccination against hepatitis B. The region with the highest coverage was Huanuco with 84,3% (95% CI: 80,8-87,2). Among newborns in public health facilities, vaccination reached 72,6%, while in private health facilities was 43,2%. Conclusions. The proportion of newborns who received vaccination against hepatitis B varies according to region, being higher among those who were born in public health facilities.